The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/19419899.2016.1189452
|View full text |Cite
|
Sign up to set email alerts
|

Australian mental health professionals’ competencies for working with trans clients: a comparative study

Abstract: Growing numbers of trans people require access to mental health services, however previous research suggests that many trans clients have negative experiences with mental health professionals. This paper reports on an Australian survey of 304 counsellors, mental health nurses, psychiatrists, psychologists, and social workers with regard to their clinical knowledge, comfort, and confidence in working with trans clients. The findings suggest that training and previous experience in working with trans clients are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Many studies throughout the literature have shown the lack of training for clinicians in transgender healthcare (Vance et al . 2015; Riggs & Bartholomaeus, 2016; Torres et al . 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies throughout the literature have shown the lack of training for clinicians in transgender healthcare (Vance et al . 2015; Riggs & Bartholomaeus, 2016; Torres et al . 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This mirrors findings in research concerning the experiences of LGB individuals in therapy (Bepko & Johnson, 2000). Given that many transgender people will experience mental health problems (Bouman et al, 2017; Price‐Fenney et al, 2020; Yang et al, 2015) and seek help from a therapist, and the reported dissatisfaction with mental health professionals (McCann & Sharek, 2016; Rees et al, 2021; Snow et al, 2019), this review adds to literature highlighting the importance of education and training for practitioners in transgender issues (e.g., Riggs & Bartholomaeus, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Incomplete surveys had less than two demographic questions answered and were therefore not included in analysis of the results. Whilst the number of all youth gender diversity specialists in Australia, including private practitioners is unknown, the number is thought to be growing (Riggs & Bartholomaeus, ). The low response rate is therefore not generalisable.…”
Section: Methodsmentioning
confidence: 99%